Dissemination of the Russian emigrant literature and the literature of the Book Program in East Europe in 1950-1990 - Alvydas Kazakevičius (Knygotyra)
Many famous Russian writers, artists, scientists, and public figures lived and worked in emigration. Some of them (M. Dobuzhinskiy, L. Karsavin, J. Mackevich Nord, T. Shuravin, A. Yashchenko, and others) lived and productively worked in independent Lithuania during the pre-war period. Russian emigration and private libraries became a haven where Russian belles-lettres (works of A. Akhmatova, M. Bulgakov, I. Bunin, L. Chukovskaya, etc.) survived.